2017
DOI: 10.1016/j.ijplas.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal plasticity and phenomenological approaches for the simulation of deformation behavior in thin copper alloy sheets

Abstract: International audienceIn the expanding context of device miniaturization, forming processes of ultra thin sheetmetals are gaining importance. Numerical simulation of these processes requires accurate material modeling. In this study, both the phenomenological modeling approach and the crystal plasticity finite element method (CPFEM) are considered. Theoretical definitions of both models, numerical implementation as well as their parameter identification procedures are outlined. Subsequently they are compared o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…It has been also observed that microstructural features influence the mechanical response of copper film. Film thickness, thermal treatments or grain size, shape and orientations, manufacturing process generate different copper mechanical behaviors, as pointed out experimentally by Schwaiger et al (2003) or Wimmer et al (2014) for PCB applications or by Adzima et al (2017) for forming process of copper thin sheet.…”
Section: Introductionmentioning
confidence: 93%
“…It has been also observed that microstructural features influence the mechanical response of copper film. Film thickness, thermal treatments or grain size, shape and orientations, manufacturing process generate different copper mechanical behaviors, as pointed out experimentally by Schwaiger et al (2003) or Wimmer et al (2014) for PCB applications or by Adzima et al (2017) for forming process of copper thin sheet.…”
Section: Introductionmentioning
confidence: 93%
“…Many experimental investigations were conducted to indicate the geometrical shapes of yield surface distortion with the remarkable corner effects in the pre-strain direction [ 9 , 10 ] and non-normality of plastic flow on the smooth yield surface [ 11 , 12 ]. At the same time, two main material constitutive models were employed to predict the anisotropic yielding and plastic flow behaviors of polycrystalline materials: the phenomenological approach introducing the anisotropic yield functions with associated or non-associated flow rule [ 13 , 14 , 15 ] and the micromechanical approach based on the polycrystalline plasticity models [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the phenomenological approach, various anisotropic yield functions based on the associated flow rule (AFR) or non-associated flow rule (non-AFR) to account for the anisotropy of yield surface evolution, Bauschinger effect, and strain-hardening behavior have been proposed [ 2 , 16 , 19 , 20 ]. The earliest and most widely used yield criteria under the associated flow rule with a single function in a quadratic or a non-quadratic form to describe both yield behavior and the direction of plastic strain were initiated by Hill [ 21 ] and Hosford [ 22 ], and the yield locus based on these yield criteria was only restricted to the plane stress states excluding shear stress terms and orthotropic symmetry assuming principal stress axes superimposed onto orthotropic axes [ 3 , 4 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The full-field models, such as crystal plasticity finite element methods (CPFEM) [5][6][7][8] enable investigating the behavior of a polycrystalline aggregate at both microscopic and macroscopic levels and allow examination of deformation flow at distinctive deformation rates and temperatures. The CPFEM with different crystal plasticity constitutive models [9][10][11] were successfully employed to simulate the deformation behavior of single crystalline materials as well as polycrystalline systems. The mean-field approximations [12][13][14][15][16], treating the material as a continuum at the level of single grain, are effective approaches to simulate the behavior of polycrystalline systems, where each grain interacts with the neighborhood in a predefined way.…”
Section: Introductionmentioning
confidence: 99%